(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The automotive industry is one of the most important sectors of the global economy today. Millions of cars are produced and sold every year, which increases competition in this industry. Developing effective marketing strategies is the key to success for companies. This article analyzes marketing strategies in the automotive industry, provides information on their importance, main directions and modern trends.